ZnO doping profile effect on CIGS solar cells efficiency and parasitic resistive losses based on cells equivalent circuit - Khoshsirat, Nima; Md Yunus, Nurul Amziah; Hamidon, Mohd Nizar; Shafie, Suhaidi; Amin, Nowshad (IEEE, 2013)
The window layer of the CIGS thin film solar cells plays the role of transparent front contact and the n-side of pn-heterojunction. Thus the variation of window layers electrical and optical properties can affect the cell performance. Properties of Al-doped Zinc oxide (ZnO) thin film as most common used window layer for CIGS solar cells were studied via simulation using the simulation program called SCAPS-1D. This study is aimed to find the effect of ZnO layer doping profile on cell performance. It is found that increasing Al-content up to 5% in ZnO layer will lead to increasing the cell efficiency and will decrease the cell series and shunt resistance.